LANDSCAPE, EXOTICISM AND LITERARY TOURISM: THE VOGUE FOR THE ROMANTIC VOYAGE TO SPAIN - Pascoal, Sara Cerqueira (2017)
If it is true that in the eighteenth century begins to bloom an intense literary activity related to travel, it will be in the next century that this activity will reach its peak, especially regarding the travels to Spain. Romantic travel books are very different from those published in the eighteenth century; a profound transformation took place in social and economic infrastructures, which would explain that even travel narratives suffered a change. The predisposition and objectives that travelers embrace changed, as the trip will be understood more as an exercise for the soul and spirit than as an exercise for the reason. Romantic travel books will then replace Grand Tour and enlightenment travel books. This article aims to reflect on these changes which have shaped, in our view, a new style, a new approach to landscape and outweigh the importance of picturesque, exotic and literary places.